Analysis of the Level of Satisfaction of Electrical Engineering Education (PTE) FT-UNM Students in the Use of the Single Academic Service System (My-Sams) Application - Wati, Hikma; Yusuf Mappeasse, Muhammad; Zulhajji, Zulhajji (Fakultas Teknik Universitas Negeri Makassar, 2025)
This study evaluates the satisfaction level of students in the Electrical Engineering Education Department, Faculty of Engineering, Makassar State University (PTE FT UNM) in using the My-SAMS (My Single Academic Management System) application based on the End User Computing Satisfaction (EUCS) model, which measures satisfaction through content, accuracy, format, ease of use, and timeliness. Using a quantitative ex post facto design, data were collected from 136 students (2018–2023 cohorts) through a 20-item Likert-scale questionnaire. The research instruments were tested for validity using the product-moment correlation and for reliability using Cronbach’s Alpha, both showing acceptable results. Data analysis employed descriptive statistics using SPSS 23 and Excel 2021 to identify satisfaction patterns. The findings showed that students were moderately satisfied with content (45%), format (54%), ease of use (57%), and timeliness (46%), while the accuracy dimension was rated dissatisfied (33%). These results suggest that while My-SAMS is user-friendly, issues remain regarding data accuracy and synchronization. It is recommended that system developers enhance data validation and integration processes and provide continuous operator training to ensure data consistency. In conclusion, the study emphasizes that My-SAMS has achieved moderate success in meeting user expectations but requires further improvements in information accuracy and reliability to strengthen trust and system performance. The findings are expected to serve as a reference for improving academic digital services and as a foundation for further research on user satisfaction in academic information systems.